An Analysis of Children's Rights to Their Parents According to Sheikh Ahmad Husain Ali Salam in the Book Huququ Al-Walidayn - Firda Azahra (Universitas Muhammadiyah Surabaya, 2025)
Abstract Research Objective – This study aims to describe the rights of children toward their parents based on the thoughts of Syekh Ahmad Husein Ali Salam in Ḥaququ al-Wālidayn. The research focuses on identifying what rights must be fulfilled by parents from the moment a child is born, and how these responsibilities shape the child’s physical, emotional, and spiritual development. Methodology – This research uses a library research approach by examining the primary text Ḥaququ al-Wālidayn and supporting studies related to child rights in Islamic education. Data were analyzed using content analysis to understand the concepts presented in classical texts and compare them with findings from contemporary scholarly works. Findings – The study reveals that every child has essential rights such as receiving a good name, breastfeeding and basic care, affection, fairness, protection from harmful environments, and early religious education. These rights are not only related to physical needs but also emotional and spiritual aspects important for developing good character. The findings also show that parents’ obligations in raising their children are lifelong, involving continuous guidance, role-modelling, and prayer. Research Implications/Limitations – This study highlights the relevance of classical Islamic teachings in today’s context and shows that fulfilling children’s rights remains a challenge, especially with modern issues such as digital exposure. The research is limited to textual analysis and does not include field data. Originality/Value – This study contributes by connecting the classical understanding of child rights from Ḥaququ al-Wālidayn with current social and technological conditions. It offers a comprehensive view of children’s rights in Islam and emphasizes the long-term responsibilities of parents in shaping a child’s character.